Ortho-xylene hydroisomerization under pressure on HMS-Ti mesoporous silica decorated with Ga2O3 nanoparticles. (15th October 2015) - Zepeda, T.A.; Pawelec, B.; Infantes-Molina, A.; Yocupicio, R.I.; Alonso-Núñez, G.; Fuentes, S.; Diaz de León, J.N.; Fierro, J.L.G.
Graphical abstract: Highlights: The Ga catalysts are highly active catalysts in the hydroisomerization of o -xylene. The Ga catalysts exhibited larger isomerization than hydrogenation of o -xylene. The hydrogen pressure led to an increase of ISO and HYD of o -xylene. The most active catalyst was prepared with Ga loading of 1.1 wt.%. Abstract: This contribution describes the effect of HMS-Ti substrate decoration with variable amounts of Ga2 O3 on the catalytic response of bifunctional Ga2 O3 /HMS-Ti catalysts in the hydroisomerization of ortho-xylene carried out in a batch reactor at 300 °C. The effect of hydrogen pressure (5, 10 and 40 bar) was investigated. The synthetized Ga2 O3 /HMS-Ti samples were characterized by variety of techniques: HRTEM, XRD, N2 adsorption–desorption isotherms, FTIR in the –OH region, TPR and XPS. The catalyst activity showed a volcano-type curve being the catalyst with Ga loading of 1.1 wt.% the most active among the catalysts studied. Both FT-IR spectra of adsorbed pyridine and HRTEM images indicated that this behavior is linked to its high Brønsted and Lewis acidities and presence of small Ga2 O3 particles homogeneously dispersed on the support surface. All catalysts exhibited larger isomerization than hydrogenation of ortho -xylene. At equilibrium, the products detected were meta - and para -xylenes, and dimethylcyclohexane (DMCH); meta -xylene being the main reaction product. An increase of hydrogen pressure from 5 to 10 bar led to an increase of isomerization and hydrogenation of ortho -xylene. Further increase of the hydrogen pressure from 10 to 40 bar had a very small effect on the catalyst activity.